Recent developments in recycling of polystyrene based plastics - Thakur, Sourbh; Verma, Ankit; Sharma, Bhawna; Chaudhary, Jyoti; Tamulevicius, Sigitas; Thakur, Vijay Kumar (Elsevier, 2018)
Due to their superior properties, plastics derived from petroleum have been extensively used almost in everyday life since last few decades. Because of lack in the manageability of plastic solid waste, their volume is increasing steadily in the natural world. Unfortunately, the disposal of plastics wastes in the oceans and land filling has led to a global issue. To effectively and efficiently deal with plastic solid waste is becoming a great challenge for the society as plastic solid waste creates big threat to our environment. Recycling of plastics solid waste should be performed to produce products having same quality to original plastics. This review article gives an overview of plastics solid waste with particular emphasis on the recent progress in polystyrene based plastics.